2022
DOI: 10.1016/j.cgh.2021.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is Associated With Increased Risk of Crohn’s disease, but not Ulcerative Colitis: A Pooled Analysis of Five Prospective Cohort Studies

Abstract: It is unclear whether obesity is associated with the development of inflammatory bowel disease despite compelling data from basic science studies. We therefore examined the association between obesity and risk of Crohn's disease (CD) and ulcerative colitis (UC). METHODS:We conducted pooled analyses of 5 prospective cohorts with validated anthropometric measurements for body mass index (BMI) and waist-hip ratio and other lifestyle factors. Diagnoses of CD and UC were confirmed through medical records or ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…[13][14][15] In line with this, prospective epidemiological studies indicated that obesity emerges as an independent risk factor for CD. 16 Preclinical and translational studies indicated that energy metabolism controls gut immune responses and that excessive intake of carbohydrates and long-chain fatty acids deteriorate or instigate gut inflammation in several mouse models. 9 In human IBD, early surgical studies from the 1990s indicated that luminal factors (potentially nutrients, microbes or related metabolites) are sufficient to evoke gut inflammation, 17 18 which led to the nowadays established therapeutic concept of ileostomy.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In line with this, prospective epidemiological studies indicated that obesity emerges as an independent risk factor for CD. 16 Preclinical and translational studies indicated that energy metabolism controls gut immune responses and that excessive intake of carbohydrates and long-chain fatty acids deteriorate or instigate gut inflammation in several mouse models. 9 In human IBD, early surgical studies from the 1990s indicated that luminal factors (potentially nutrients, microbes or related metabolites) are sufficient to evoke gut inflammation, 17 18 which led to the nowadays established therapeutic concept of ileostomy.…”
Section: Introductionmentioning
confidence: 99%
“…It could be hypothesized that the weight loss and not the surgery itself, triggers the new onset CD is some patients. However, other studies have shown a relationship between obesity and a higher risk of developing CD [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…IF interventions appeared to confer health benefits independent of energy intake ( Figure 1 ) [ 2 , 3 , 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. For example, in two separate trials of overweight women, participants lost the same amount of weight during a 6-month period whether they followed an IF intervention or a 25% energy-restricted diet.…”
Section: Potential Mechanisms Of Action For Intermittent Fasting Effectsmentioning
confidence: 99%